ENSINO DE BIM EM UM CURSO DE ARQUITETURA E URBANISMO: AVALIAÇÃO DA PERCEPÇÃO DE DEMANDA - Kehl, Caroline; Stumpf, Cauã; Rosa, Douglas Cassius; Freitas, Anderson; Isatto, Eduardo Luis (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Despite its enormous impact on the design, construction and maintenance of buildings, Building Information Modeling (BIM) has been very slowly introduced in Brazilian undergraduate courses. In this context, this article aims to evaluate the degree of familiarity of undergraduate students of an architecture course with BIM, in order to assist planning of strategies for the introduction of this content in the curriculum. The method used include phase 1 - literature review, through which other similar experiences were studied; phase 2 - descriptive - when evidence is presented regarding the implementation of the theme in the curricular structure and course subjects; and phase 3 - exploratory phase, in which a survey was applied to students. By relating the results of the literature review with evidence collected in phase 2 and the survey, it is possible to establish comparisons and to speculate about further barriers and opportunities. For that reason, the paper intends to suggest recommendations for the inclusion of BIM in Architecture and Urbanism courses.